Graves' disease coexisting with resistance to thyroid hormone: a rare case. Issue 2 (29th December 2017) - Sun, Hongping; Xu, Shuhang; Xie, Shaofeng; Cao, Wen; Chen, Guofang; Di, Hongjie; Zheng, Rendong; Li, Xingjia; Mao, Xiaodong; Liu, Chao
Key Clinical Message: A rare case of resistance to thyroid hormone (RTH) complicated with Graves' hyperthyroidism was reported. The management of this disease is similar to that of Graves' disease. Antithyroid drug therapy is the first choice, and iodine therapy and surgery are not recommended due to the possibility of severe hypothyroidism and enlargement of the pituitary gland. Abstract : A rare case of resistance to thyroid hormone (RTH) complicated with Graves' hyperthyroidism was reported. The management of this disease is similar to that of Graves' disease. Antithyroid drug therapy is the first choice, and iodine therapy and surgery are not recommended due to the possibility of severe hypothyroidism and enlargement of the pituitary gland.